Ձվարանների դիսեմինացված քաղցկեղ. վիրահատությո՞ւն, թե՞ քիմիաթերապիա - Ջիլավյան, Գ. Ա.; Ջիլավյան, Ար. Գ.; Հարությունյան, Լ. Ա (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Преимущество неоадъювантной химиотерапии особенно очевидно при анализе продолжительности выживаемости пациентов с III стадией. Пациенты, получавшие радикальную операцию по схеме неоадъювантная химиотерапия+операция, живут на 19,4 мес. дольше – 70,3 мес., а пациенты, прооперированные в первичном этапе – 50,9 мес. Медиана выживаемости больных в первой группе также была выше и составила 48 мес. по сравнению с 30 мес. во второй группе (р<0,05). The benefit of neoadjuvant chemotherapy is especially evident when analyzing the survival time of patients with stage III disease. Patients who received radical surgery according to the scheme of neoadjuvant chemotherapy + surgery, live 19,4 months longer – 70,3 months, and patients operated on in the primary stage – 50,9 months. The median survival of patients in the first group was also higher and amounted to 48 months compared to 30 months in the second group (p<0,05).
Keywords: Կլինիկական բժշկություն